Role of Alpha Lipoic Acid in Oxidant /Antioxidant Status and Gene Expression of Glutathione Reductase in Hydrogen Peroxide Exposed Rats: (Part -2) - Al-Okialy, Baraa Najim; Saleh Alwan, Mohammad (The Iraqi Journal of Veterinary Medicine, 2019)
This study was designated to evaluate the protective role of alpha lipoic acid against oxidative stress resulted by hydrogen peroxide on some oxidants/ antioxidants parameters and gene expression of glutathione peroxidase in adult Wistar rats. Forty adult male rats were randomly divided into four equal groups (10 rats /group) and were handled daily as follows for 56 days : Control group were intubated distal water and received ordinary tap water ; group T1 were intubated 60mg/kg B.W of alpha lipoic acid and received ordinary tap water ; group T2 were received hydrogen peroxide in tap water at concentration of 0.5% , while group T3 were intubated 60mg/kg B.W of alpha lipoic acid and received ordinary tap water containing 0.5% hydrogen peroxide. Fasting blood samples were collected at 0, 28 and 56 days of experimental periods for measurement of serum peroxynitrite and malondialdehyde concentrations, as well catalase activity. Furthermore, gene expression of glutathione reductase in liver was investigated. Administration of 0.5% hydrogen peroxide in drinking water (group T2) manifested a significant elevation in serum peroxynitrite and malondialdehyde with significant decrease in catalase and Glutathione, concentrations. Also, a significant decrease in gene expression of glutathione reductase was observed as compared to other treated groups. Nevertheless, rats in group T3 shows a significantly improvement in oxidant /antioxidant status with increase in folds changes of gene expression of glutathione reductase as compared to control and T2. In conclusion, supplementation of alpha lipoic acid to rats significantly reduced oxidative stress –induced by hydrogen peroxide and caused improvement of gene expression of glutathione reductase in liver via its antioxidant properties.